Chesapeake Bay Inorganic Carbon: Spatial Distribution and Seasonal Variability - Brodeur, Jean R.; Chen, Baoshan; Su, Jianzhong; Xu, Yuan-Yuan; Hussain, Najid; Scaboo, K. Michael; Zhang, Yafeng; Testa, Jeremy M.; Cai, Wei-Jun (Frontiers in Marine Science, 2019)
Few estuaries have inorganic carbon datasets with sufficient spatial and temporal coverage for identifying acidification baselines, seasonal cycles and trends. The Chesapeake Bay, though one of the most well-studied estuarine systems in the world, is no exception. To date, there have only been observational studies of inorganic carbon distribution and flux in lower bay sub-estuaries. Here, we address this knowledge gap with results from the first complete observational study of inorganic carbon along the main stem. Dissolved inorganic carbon (DIC) and total alkalinity (TA) increased from surface to bottom and north to south over the course of 2016, mainly driven by seasonal changes in river discharge, mixing, and biological carbon dioxide (CO2) removal at the surface and release in the subsurface. Upper, mid- and lower bay DIC and TA ranged from 1000-1300, 1300-1800, and 1700-1900 µmol kg-1. The pH range was large, with maximum values of 8.5 at the surface and minimums as low as 7.1 in bottom water in the upper and mid-bay. Seasonally, the upper bay was the most variable for DIC and TA, but pH was more variable in the mid-bay. Our results reveal that low pH is a continuing concern, despite reductions in nutrient inputs. There was active internal recycling of DIC and TA, with a large inorganic carbon removal in the upper bay and at salinities <5 most months, and a large addition in the mid-salinities. In spring and summer, waters with salinities between 10 and 15 were a large source of DIC, likely due to remineralization of organic matter and dissolution of CaCO3. We estimate that the estuarine export flux of DIC and TA in 2016 was 40.3 + 8.2 × 109 mol yr-1 and 47.1 + 8.6 × 109 mol yr-1. The estuary was likely a large sink of DIC, and possibly a weak source of TA. These results support the argument that the Chesapeake Bay may be an exception to the long-standing assumption that estuaries are heterotrophic. Furthermore, they underline the importance of large estuarine systems for mitigating acidification in coastal ecosystems, since riverine chemistry is substantially modified within the estuary.